1996
DOI: 10.1007/bf02199801
|View full text |Cite
|
Sign up to set email alerts
|

Allelic diversity at the primateMhc-G locus: Exon 3 bears stop codons in allCercophitecinae sequences

Abstract: Twenty-seven major histocompatibility complex (Mhc)-G exon 2, exon 3, and exon 2 and 3 allelic sequences were obtained together with 12 different intron 2 sequences. Homo sapiens, Pan troglodytes, Pan paniscus, Gorilla gorilla, Pongo pygmaeus, Macaca fascicularis, Macaca mulatta, and Cercopithecus aethiops individuals were studied. Polymorphism does not follow the classical pattern of three hypervariable regions per domain and is found in all species studied; exon 3 (equivalent to the alpha 2 protein domain) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Compared to the classical class I loci, Mhc-G is less polymorphic and is restricted in its expression to the extravillous trophoblast (Kovats et al, 1990). Although there is some evidence for transspecies polymorphism at this locus (Castro et al, 1996), it has not been well documented that the polymorphism is maintained by balancing selection. Since there is only one informative site, there is no reason to exclude this locus from the analysis.…”
Section: Eight Loci That Support the (Cg)h Phylogenymentioning
confidence: 97%
“…Compared to the classical class I loci, Mhc-G is less polymorphic and is restricted in its expression to the extravillous trophoblast (Kovats et al, 1990). Although there is some evidence for transspecies polymorphism at this locus (Castro et al, 1996), it has not been well documented that the polymorphism is maintained by balancing selection. Since there is only one informative site, there is no reason to exclude this locus from the analysis.…”
Section: Eight Loci That Support the (Cg)h Phylogenymentioning
confidence: 97%
“…There is close homology of implantation and placentation among the Old World primates (35). The rhesus monkey MHC contains orthologs of the human classical MHC class I loci Mamu-A and -B, and the nonclassical loci Mamu-E, -F, and -G (14,20,25,(36)(37)(38). The identification of a novel MHC class I locus expressed in the rhesus monkey placenta that shares unique molecular characteristics of HLA-G (14) and has a tissue distribution closely matching that seen for HLA-G (16) provides a unique opportunity for the study of nonclassical MHC class I molecules in the primate placenta.…”
Section: Discussionmentioning
confidence: 99%
“…MHC-G has been described in some nonhuman primates. [2728293031] It has been mentioned that in chimpanzee ( Pan troglodytes ) MHC-Ib is known to be organized in similar way as human MHC-Ib. [32] It has also been described in case of many other nonhuman primate species.…”
Section: Gene Organization and Evolutionary Perspective Of Nonclassicmentioning
confidence: 99%
“…[31] Phylogenetic study comprising exon 2, exon 3, and intron 2 sequences of MHC-G of 7 nonhuman primates along with HLA-G have shown that cotton top tamarin ( Saguinus oedipus ) MHC-G sequences are more closer to human and great apes (Pongids). [30]…”
Section: Gene Organization and Evolutionary Perspective Of Nonclassicmentioning
confidence: 99%
See 1 more Smart Citation